Uji Aktivitas Antibakteri Air Perasan Jeruk Siam Sambas terhadap Escherichia coli - Bimo Hendrayana; Mistika Zakiah; Syarifah Nurul Yanti Rizki Syahab Assegaf; Delima Fajar Liana; Mahyarudin Mahyarudin (Lembaga Pengembangan Kinerja Dosen, 2025)
Escherichia coli is a bacterium that typically resides as a normal flora in the gastrointestinal tract of humans and animals. However, certain strains of E. coli can cause infections in humans. Therefore, antibiotics are needed to inhibit the growth of these infection-causing bacteria. The increasing cases of antibiotic resistance in E. coli necessitate alternative therapies, including the use of natural substances. In West Kalimantan, one potential source is the Pontianak Orange (Citrus nobilis var. microcarpa). This plant contains secondary metabolites that can be used for medicinal purposes, such as the juice extract. The compounds within these secondary metabolites possess antimicrobial properties that could be used as antibacterials. To determine the antibacterial potential of Pontianak Orange juice (Citrus nobilis var. microcarpa) against Escherichia coli. This study utilized an experimental design featuring a post-test only group design. Phytochemical analysis indicated that Pontianak Orange juice (Citrus nobilis var. microcarpa) contains phenolics (+), alkaloids (+), and terpenoids (++). Antibacterial activity testing at all concentrations (25%, 50%, 75%, and 100%) showed no inhibition zones. The juice of Pontianak Orange (Citrus nobilis var. microcarpa) did not show antibacterial effects against the growth of Escherichia coli bacteria.